2015
DOI: 10.1111/cid.12385
|View full text |Cite
|
Sign up to set email alerts
|

In‐Vitro Study of the Contamination Remaining on Used Healing Abutments after Cleaning and Sterilizing in Dental Practice

Abstract: Reuse of healing abutments between patients should be reevaluated in light of this data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 16 publications
2
54
0
1
Order By: Relevance
“…It is possible that this residue is bacteria based, which could explain the small areas of oxidative discoloration on the surface, as bacterial metabolites are known to induce oxidation on titanium surfaces . Additionally, the presence of biological debris even after the cleaning and sterilization performed in the study may provide rationale to re‐evaluate the common practice of re‐using healing abutments clinically, as the effects of these residual organic materials on peri‐implant tissues is not known …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It is possible that this residue is bacteria based, which could explain the small areas of oxidative discoloration on the surface, as bacterial metabolites are known to induce oxidation on titanium surfaces . Additionally, the presence of biological debris even after the cleaning and sterilization performed in the study may provide rationale to re‐evaluate the common practice of re‐using healing abutments clinically, as the effects of these residual organic materials on peri‐implant tissues is not known …”
Section: Discussionsupporting
confidence: 76%
“…The detection of nitrogen, calcium, and phosphorus in addition to generally present carbon and oxygen results suggests that this residue is biological and not just the carbonaceous contamination found on all surfaces . Because a portion of the IHAs are exposed to the oral environment during placement, the source of this residue could be bacterial plaque, bolus, soft‐tissue, or a variety of protein based compounds present in saliva that have adhered to the surface . It is important to note that formation of bacterial biofilm starts with a conditioning layer adsorbed onto the titanium surface of glycoproteins, Ca 2+ , Mg 2+ , and water which early colonizers use to adhere to the surface of titanium.…”
Section: Discussionmentioning
confidence: 99%
“…It was also important to underline how the re-use of HAs among different patients, mainly for economic reasons, may have effects on the early inflammation of the peri-implant tissues linked to the residues present after the common sterilization cycles. In two different studies [45,46], authors studied the effect of re-use of HAs in clinical practices. Wadhwani et al [45] showed that the healing screws treated according to the standard cleaning and sterilization protocols for subsequent uses showed residues protein contamination at one or more sites in 90% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…In two different studies [45,46], authors studied the effect of re-use of HAs in clinical practices. Wadhwani et al [45] showed that the healing screws treated according to the standard cleaning and sterilization protocols for subsequent uses showed residues protein contamination at one or more sites in 90% of cases. Also, Stacchi et al [46] demonstrated a better cell binding in HAs treated with specific cleaning methods compared with the control re-used screws and treated with standard methods.…”
Section: Discussionmentioning
confidence: 99%
“…In dentistry, there are several devices that are reused across patients encompassing all dental specialties, such as surgical instruments, burs, bone saws, endodontic files, periodontal instruments, orthodontic devices, x‐ray holders, and several instruments in pediatric dentistry. In implant dentistry, common examples of ad‐hoc reusable devices include surgical instruments, surgical handpieces, surgical drills, bone cutting burs, impression copings, and many more . Examples of in‐situ reusable devices in implant dentistry include healing abutments, cover screws, abutments, abutment screws, and prosthetic screws.…”
mentioning
confidence: 99%